The Global Climate and Environmental Protest: Student Environmental Activism a Transformative Defiance - DAMOAH, Benjamin; KEENGWE, Sagini; OWUSU, Samuel; YEBOAH, Clement; KEKESSIE, Francis (International Journal of Environmental, Sustainability, and Social Science, 2023)
Global climate and environmental protests are a widespread movement that aims to draw attention to the urgent need for action on climate change and environmental issues. The movement has gained momentum in recent years, as people around the world have become increasingly aware of the devastating effects of climate change, such as rising sea levels, more frequent and severe natural disasters, and loss of biodiversity. This paper is theoretically grounded on social movement theory which navigated through several climate protests witnessed in recent times, particularly in sub-Sahara Africa. More than 7 million young people gather in cities throughout the globe in protest of the lack of action by world leaders to stop the severe effects of climate change and its accelerating rate. To put pressure on world leaders to act, Greta Thunberg, a Swedish climate activist, and others call on students to leave their classes on Fridays to protest the unending climate crises. These campaigns have led to growing environmental activism as more young people are becoming aware of the devastating impact of climate change on their daily lives. It was discovered that; Students have been actively involved in several climate protests defying the institution’s authorities to protest for a change in the global conversation amid a series of rhetoric and indecision from world leaders. The paper has unearthed that, climate activism has yielded positive outcome which has brought transformation into global discourse in pursuit of strategic measures to address climate and environmental crises.